Pengaruh Kuantitas Tanaman Melati Air (Echinodorus palaefolius) sebagai Fitoremediator Limbah Cair Penyamakan Kulit Proses Tanning - Alya Rahmaisyanti; Yuli Astuti Hidayati; Andry Pratama (Jurnal Teknologi Hasil Peternakan, 2022)
Phytoremediation is an effort to restore polluted land by absorbing, degrading, removing, stabilizing, or transforming pollutants using hyperaccumulator plants. Mexican Sword plants in phytoremediation are used as hyperaccumulators that can reduce heavy metal content by rhizofiltration mechanism. This study aims to determine the effect of mexican sword plant quantity on chromium concentration, pH value, and Dissolved Oxygen (DO). The research was conducted using an experimental method using a Completely Randomized Design (CRD), with 4 treatments, P0 = 0 mexican sword plants, P1 = 4 mexican sword plants, P3 = 6 mexican sword plants, P4 = 8 mexican sword plants. Repetition was carried out five times for each treatment. The data obtained were analyzed statistically by Analysis of Variance at = 5% and if there is a significant difference, further tests will be carried out using the Tukey test. The results showed that there was a significant difference (P<0.05) for each quantity of mexican sword plants concerning chromium concentration, pH value, and Dissolved Oxygen (DO). The best treatment results were shown by the quantity of 6 individuals (P2) with a Chromium concentration of 16.87 mg/L, a pH value of 8.45, and a DO of 1.3%.